Co-cultivation of two freshwater microalgae species to improve biomass productivity and biodiesel production. (15th September 2019) - Rashid, Naim; Ryu, Ae Jin; Jeong, Ki Jun; Lee, Bongsoo; Chang, Yong-Keun
Graphical abstract: Highlights: Co-cultivation of two microalgae species ( Ettlia and Chlorella ) was tested. Co-cultivation returned the maximum biomass productivity at 1:08 inoculation ratio. Biomass productivity in mono-culture was 0.26 g L −1  day −1 . Biomass productivity in co-cultivation was 0.70 g L −1  day −1 . Co-cultivation was more effective in mixotrophic condition than autotrophic. Abstract: This study aimed to investigate the symbiotic relationship of two freshwater microalgae species, Ettlia sp. and Chlorella sp . HS-2 to improve biomass productivity . The species were co-cultivated autotrophically under the inoculation ratios ( Chlorella / Ettlia ) of 1:01, 1:04, 1:08, and 1:16. The performance of co-cultivation was compared with monoculture. It found that the co-cultivation returned higher biomass productivity (P < 0.05) than the monoculture under all inoculation ratios. The highest biomass productivity of 0.70 ± 0.02 g L −1  day −1 was achieved with an inoculation ratio of 1:08. The biomass productivity further increased to 0.74 ± 0.06 g L −1  day −1 by switching the cultivation mode to the mixotrophic condition. The biomass productivity of mixotrophic co-cultivation was higher P < 0.05 (0.74 ± 0.06 g L −1  day −1 ) than the mixotrophic mono-culture of Ettlia (0.41 ± 0.06 g L −1  day −1 ) but equal to mixotrophic mono-culture of Chlorella . FACS analysis revealed that the biomass obtained after co-cultivation contained 81% of Chlorella cells. In biochemical composition, co-cultivation (autotrophic) biomass contained protein 41%, carbohydrates 33%, lipids 11%, and pigments 2% of dry cell weight. The major fatty acids produced in the co-cultivation were C16–C18, which are favorable for biodiesel production. It is concluded that the co-cultivation is more favorable than the monoculture to obtain high biomass productivity and stable biomass composition.